The neurocognition of translation and interpreting - García, Adolfo Martín (Benjamins translation library, 2019)
This work offers a comprehensive account of brain-based research on translation and interpreting. First, the volume introduces the methodological and conceptual pillars of psychobiological approaches vis-à-vis those of other cognitive frameworks. Next, it systematizes neuropsychological, neuroscientific, and behavioral evidence on key topics, including the lateralization of networks subserving cross-linguistic processes; their relation with other linguistic mechanisms; the functional organization and temporal dynamics of the circuits engaged by different translation directions, processing levels, and source-language units; the system?s susceptibility to training-induced plasticity; and the outward correlates of its main operations. Lastly, the book discusses the field?s accomplishments, strengths, weaknesses, and requirements. Its authoritative yet picturesque, didactic style renders it accessible to researchers in cognitive translatology, bilingualism, and neurolinguistics, as well as teachers and practitioners in related areas. Succinctly, this piece establishes a much-needed platform for translation and interpreting studies to fruitfully interact with cognitive neuroscience.